Exploring the Moderating Role of Firm Size on Corporate Governance and CSR Disclosure in Indonesian Listed Companies - Reschiwati Reschiwati; Idayanti Idayanti; Fran Sayekti (Greenation International Journal of Economics and Accounting, 2026)
This study investigates the determinants of Corporate Social Responsibility (CSR) disclosure by examining the influence of Good Corporate Governance (GCG) mechanisms and profitability, with firm size acting as a moderating variable. The governance mechanisms are represented by board size, institutional ownership, and managerial ownership. The research focuses on consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a purposive sampling method, 34 companies were selected, resulting in 170 panel data observations analyzed through panel regression using EViews 12. The findings reveal that board size, institutional ownership, and managerial ownership negatively affect CSR disclosure, while profitability has a positive effect. Furthermore, firm size only strengthens the relationship between managerial ownership and CSR disclosure, but does not moderate the effects of board size, institutional ownership, or profitability. These results indicate that larger firms tend to enhance the role of managerial ownership in encouraging broader CSR practices. This study contributes to the existing literature by providing empirical evidence on the moderating role of firm size in the relationship between corporate governance mechanisms and CSR disclosure in emerging markets. From the perspective of legitimacy theory, CSR disclosure serves as a strategic instrument for maintaining social legitimacy, strengthening stakeholder trust, and supporting long-term business sustainability. The findings are expected to provide insights for corporate management, investors, and policymakers in improving governance quality and CSR transparency.